2007
DOI: 10.3748/wjg.13.6203
|View full text |Cite
|
Sign up to set email alerts
|

Combination of allopurinol and hyperbaric oxygen therapy: A new treatment in experimental acute necrotizing pancreatitis?

Abstract: AIM:To investigate the individual and combined effects of allopurinol and hyperbaric oxygen (HBO) therapy on biochemical and histopathological changes, oxidative stress, and bacterial translocation (BT) in the experimental rat acute pancreatitis (AP). METHODS:Eighty-five Sprague-Dawley rats were included in the study. Fifteen of the eighty-five rats were used as controls (sham, GroupⅠ). AP was induced via intraductal taurocholate infusion in the remaining seventy rats. Rats that survived to induction of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Indeed there is data on successful results achieved by administering allopurinol into the peritoneal cavity of experimental animals with formed acute necrotizing pancreatitis. 15 It is possible to object to this group when one considers that the effect of allopurinol is different from that of Sterile Novuxol (Abbott). But the other reason for forming this group was to investigate the effects of the toxicity of Sterile Novuxol (Abbott) on peritoneal and abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed there is data on successful results achieved by administering allopurinol into the peritoneal cavity of experimental animals with formed acute necrotizing pancreatitis. 15 It is possible to object to this group when one considers that the effect of allopurinol is different from that of Sterile Novuxol (Abbott). But the other reason for forming this group was to investigate the effects of the toxicity of Sterile Novuxol (Abbott) on peritoneal and abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Recent evidence suggests that allopurinol improves endothelial function by profoundly reducing vascular oxidative stress and not by lowering uric acid. [7] Animal experiments have also suggested that allopurinol exerts positive effects in the treatment of major intra-abdominal surgery, [8] acute necrotizing pancreatitis, [9] chronic pancreatitis, [10] as well as in the prevention of esophageal stricture from caustic burn. [11] Diabetic rats treated with allopurinol showed improved nerve and vascular function.…”
Section: Mechanism Of Action Of Allopurinolmentioning
confidence: 99%
“…Allopurinol decreases pancreatic injury in experimental AP and has been shown to decrease the incidence of post-ERCP pancreatitis in a randomized controlled trial. 61, 62 …”
Section: Novel Therapeutic Strategies In Apmentioning
confidence: 99%